2019
DOI: 10.18805/lr-4116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed priming on growth and seed yield in kabuli chickpea (Cicer arietinum L.) varieties

Abstract: The field experiment was carried out at Water and Land Use Management Institute (WALMI) Farm, University of Agricultural Sciences, Dharwad during 2015-16 and 2016-17 to study the effect of seed priming on growth and seed yield in kabuli chickpea varieties. The experiment was laid in split plot design with three replications constituting two kabuli chickpea varieties and nine seed priming treatments. The results of pooled data revealed that, kabuli chickpea variety BG1105(V1) recorded significantly higher value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
4
3
0
Order By: Relevance
“…The above results are in tune with the Pavan et al, (2018) in Kabuli chickpea reported that seedling vigour index is said to be the product of seed germination and total seedling length (root + shoot length) and ultimately resulted in higher seed vigour. Similar results are reported by Seema et al, (2017) and Pavan et al, (2018) in Kabuli chickpea who reported that seeds treated with mancozeb (50 %) + carbendazim (25 %) have recorded highest seedling vigour index.…”
Section: Resultssupporting
confidence: 85%
“…The above results are in tune with the Pavan et al, (2018) in Kabuli chickpea reported that seedling vigour index is said to be the product of seed germination and total seedling length (root + shoot length) and ultimately resulted in higher seed vigour. Similar results are reported by Seema et al, (2017) and Pavan et al, (2018) in Kabuli chickpea who reported that seeds treated with mancozeb (50 %) + carbendazim (25 %) have recorded highest seedling vigour index.…”
Section: Resultssupporting
confidence: 85%
“…Chickpea seeds have very soft, delicate seed coat that are sensitive and prone to damage by both biotic and abiotic factors from invading and survival of wide range of fungal pathogens around rhizosphere throughout the crop period and provides a favorable condition by enhancing sufficient nutrient uptake from rhizosphere through better root system. Shinde et al (2020). These results are in conformation with the findings of Anitha et al (2013) in Soybean and Xalxo et al (2007) in chickpea.…”
Section: Volume Issuesupporting
confidence: 90%
“…Treatment carbendazim 25% + mancozeb 50% WS @ 3.5 g/kg of seed (T 2 ) recorded an higher increase in the yield to the extent of (36.00%) followed by T 3 (33.53%) , T 1 (31.93%) , T 7 (24.52%) respectively over control and yield parameters these parameters where shown higher by seed treatment with carbendazim 25% + mancozeb 50% WS @ 3.5 g/kg of seed (T 2 ) with various parameter i.e., seed yield/plant (7.61 g), seed yield/ plot (1.02 kg) increase in yield was due to increase in number of pods/plant (60.73), seed yield/plant (8.21 g), seed yield/plot (1.04 kg) this treatment was followed by (T 3 ) thiophanate methyl 45% + pyraclostrobin 5% FS @ 4 ml per kg of seeds where number of pods/plant (59.88). Increased in yield parameters may be due to seed treatment which improves seed germination, uniform plant stand and exposure of these plants for proper harnessing of sunlight, photosynthesis and its translocation of food metabolites to different growing parts and leading to better vegetative growth resultung increased number of primary and secondary branches per plant which add together for production of more number of flowers, pods, seeds per pod and test weight of seed leading to higher seed yield per plant and per ha (Shinde andHunje, 2020, Rasool et al, 2015). The results are in conformity with findings of Durga et al (2013) in chickpea.…”
Section: Resultsmentioning
confidence: 99%
“…by Golenzani et al (2012), Mehari (2015) and Shinde and Hunje (2020). Hence study indicated, the beneficial effect of potassium nitrate over dry seeds in terms of yield.…”
Section: Grain Straw Yield (Kg/ Ha) and Harvest Indexmentioning
confidence: 60%